How Do the TWO STAY TWO STRAY and Motivation Model Learning Affect Civic Education Result? - Risna Sinaga; Reh Bungana Br. Perangin-angin; Aman Simaremare Simaremare (Randwick International of Education and Linguistics Science Journal, 2024)
The teacher-centered approach has led students to feel bored and uninterested in the taught material. By choosing an appropriate learning model, it is hoped that a better understanding and interest in students will emerge, fostering a deep learning motivation. In this study, the chosen learning models were Two Stay Two Stray and Inquiry. The objectives of this research were: 1) to determine the difference in Civic Education learning outcomes between student groups taught with the Two Stay Two Stray and Inquiry learning models, 2) to examine the difference in Civic Education learning outcomes between student groups with high and low learning motivation, and 3) to investigate the interaction between the learning model and learning motivation in influencing Civic Education learning outcomes. The research was conducted at SDN 091713 Amborokan, involving fourth-grade students as the research sample. The research method employed was experimental research, utilizing a 2x2 factorial design. There were two classes involved in the study: an experimental class (IV-A) and a control class (IV-B). Data collected included Civic Education learning outcomes and student motivation data. The results of the research indicated that: 1. the learning strategy significantly influenced Civic Education learning outcomes with an F value of 58.775, 2. learning motivation significantly influenced Civic Education learning outcomes with an F value of 92.04, and 3. there was an interaction between the learning strategy and learning motivation significantly affecting Civic Education learning outcomes with an F value of 4.09. This study concludes that the selection of an appropriate learning model positively influences learning outcomes and motivation in students. It is recommended that teachers, as facilitators, should be capable of choosing suitable teaching methods to create an effective learning environment.